A Study on Sustainable Waste Management Facilities (Reception Facilities) at Ports: A Case Study of Tanjung Priok Port - Fahmi, Yunita; Agustina, Haruki; Frimawaty, Evi (Pelopor Publikasi Akademika, 2025)
This study investigates the effectiveness of hazardous (B3) and non-hazardous (Non-B3) waste management at Tanjung Priok Port through the implementation of Reception Facilities (RF) to support the Green Port initiative. Although the RF infrastructure complies with the Ministerial Regulation of Environment (Permen LH) No. 05 of 2009, Article 5, its utilization remains significantly low at only 0.27%. This inefficiency is attributed to high operational costs, limited awareness among ship operators, and insufficient waste processing capacity. Waste composition is dominated by hazardous materials such as used lubricant oil, sludge oil, and solid oil slop, while non-hazardous waste includes domestic, plastic, and organic waste. Furthermore, only 52% of personnel are adequately trained in waste management practices, highlighting a critical human resource gap. Used SWOT analysis, the strategic position of the RF system falls within the Strength–Threat (S–T) quadrant, indicating the need for a defensive diversification strategy. This strategy emphasizes leveraging existing infrastructure and regulatory compliance to address external challenges such as policy enforcement and operational constraints. The findings suggest improving RF utilization through cost reduction, stakeholder engagement, and capacity building will enhance the port’s environmental performance. This study contributes to the broader implementation of Sustainable Development Goals (SDGs) 6 (clean water and sanitation), 12 (responsible consumption and production), and 14 (life below water), offering a replicable framework for other ports in Indonesia and globally.